Changes in The Use Of Gending Kebo Giro To Hadrah Shalawat Nabi Mahallul Qiyam In Temu Manten Tradition in Bumi Mulya Kuantan Singingi Regency Riau Province - Sari, Renita; Sriwulan, Wilma; Awerman, Awerman; Wijaksana, Bambang (Musica: Journal of Music, 2024)
Temu Manten is a tradition in the traditional Javanese wedding procession. Temu Manten in Javanese means bring together bride and groom at the bride's residence in a part of traditional wedding processions. When the Temu Manten procession takes place, used Gending Kebo Giro as a music accompaniment at Temu Manten tradition. Gending Kebo Giro is played starting from the beginning of the procession until the Temu Manten tradition ends. Over time, the Temu Manten tradition in Bumi Mulya has undergone several significant changes, one of which is the change of musical accompaniment to the Temu Manten procession. Musical accompaniment which usually uses Gending Kebo Giro is currently replaced by Hadrah Sholawat Nabi Mahalul Qiyam. This study uses a qualitative research method using ethnography as a  approach. Data collection was carried out through literature study, observation, and interviews. Through the theory of change by Gerth and Mills as the main theory, the research results show that: changes in the use of gending to hadrah are caused by several factors including inter-ethnic marriage, the influence of Malay culture, and reasons for spending much amount of material.